Comparative evaluation of porcine and bovine bone xenografts in bone grafting: a systematic review and meta-analysis - Kun Wang; Jiatong Zhang; Mengyao Ding; Yifan Xie; Yan Wang; Chuyi Jin; Mengqing Yan; Lipei Liu; Cheng Ding; Xing Chen (International Journal of Implant Dentistry)
Abstract Objective To compare the efficacy of porcine bone xenografts (PBX) and bovine bone xenografts (BBX) in maxillary sinus floor augmentation (MSFA) and alveolar ridge preservation (ARP), focusing on histomorphometric and radiographic outcomes. Materials and methods A comprehensive online search for relevant studies was conducted using PubMed, Cochrane Library, Web of Science, and Scopus, including literature published up to April 2025 (PROSPERO CRD42024628683). The percentage of newly formed bone (NFB) served as the primary outcome. Secondary outcomes included histomorphometric results such as residual bone graft (RBG) and connective tissue (CT), as well as radiographic results, including vertical height reduction, horizontal width reduction, and volume reduction. Results Out of 577 initially identified records, 10 studies were included. The analysis included 239 sites grafted with BBX (51 in MSFA, 188 in ARP) and 213 sites with PBX (51 in MSFA, 162 in ARP). A total of 6 studies reported data on NFB across 202 grafted sites (101 PBX, 101 BBX). The meta-analysis found no significant difference in NFB between PBX and BBX (WMD = 1.5, 95% CI: −1.46 to 4.46; p = 0.321), with moderate heterogeneity (I² = 44.6%). For each secondary outcome, no statistically significant difference was shown between the two groups. Conclusion This systematic review found no significant differences in histomorphometric and radiographic outcomes between PBX and BBX in bone grafting (MSFA/ARP), supporting the clinical comparability of PBX as an alternative to BBX. Further well-designed randomized controlled trials are needed to evaluate long-term outcomes such as implant survival, graft resorption, and bone stability. Clinical trial number Not applicable.